MULTIVARIATE ANALYSIS USING GAMMA SPECTROMETRIC AND GEOCHEMICAL DATA IN AREA OF SUGAR CANE PLANTATION IN THE STATE OF PARANÁ/BRAZIL - Becegato, Valter Antonio; Onofre, Sideney Becker; Cabral, João Batista Pereira; Figueiredo, Olívia Aparecida Rodolfo (Geoambiente On-line, 2013)
Multivariate analysis was used in area of sugar cane plantation in the State of Paraná (Brazil) in order to understand the correlations between K, U and Th radionuclide and geochemical data for soil samples collected at 0 – 20 cm and 20 – 40 cm depths. To determine the K, U and Th radionuclide concentrations is soils, fertilizers and gypsum, a Syntrex/Geofyzika GS-512 gamma-ray spectrometer with 512 channels was used, with energy ranging from 0.1 to 3 MeV. The minimum and maximum concentrations found in soils for K, U and Th radionuclide were respectively 31 – 124 Bq Kg-1; 0 - 12.3 Bq Kg-1; 0 – 17.1 Bq Kg-1. The maximum variation corresponded to uranium (56%). Geochemical data for clay, organic matter, phosphorous, potassium, calcium, magnesium, copper, zinc, iron, manganese, and pH at the 0 – 20 cm depth were respectively: 12 – 30; 0.4 – 1.4; 1.2 – 80; 6 – 132; 0.5 – 3.1; 0.2 – 4.1; 0.2 – 14.2; 4 – 155; 15.6 – 16.1, and 6.7 – 7.5. At 20 – 40 cm depth: 12 – 30; 0.3 – 1.1; 1.4 – 80; 7 – 200; 0.4 – 2.4; 0.1 – 0.9; 0.2 – 2.8; 0.1 – 12.6; 4.3 – 114; 18.9 – 149, and e 6.5 – 7.6. Correlation exists between radionuclide and geochemical data were obtained at both depths.